TIDAL WAVE PERIOD AND SEISMICITY - Morgounov V.A.; Boyarsky E.A.; Stepanov M.V. (My University, 2006)
We have attempted to analyze the relationship between tide and seismicity with due regard for the development of creep in the Earth’s crust, which depends on the strain duration and, hence, on the harmonic period. We studied the distribution of earthquake moments by tidal phases in 130 000 events for the years 1970–2003. To obtain statistically significant results, we used catalogs of earthquakes in the nine most active seismic regions of the Earth.